2018
DOI: 10.1111/medu.13783
|View full text |Cite
|
Sign up to set email alerts
|

Developing a video‐based method to compare and adjust examiner effects in fully nested OSCEs

Abstract: Background Although averaging across multiple examiners’ judgements reduces unwanted overall score variability in objective structured clinical examinations ( OSCE ), designs involving several parallel circuits of the OSCE require that different examiner cohorts collectively judge performances to the same standard in order to avoid bias. Prior research suggests the potential for important examiner‐cohort effects in distributed or national exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 59 publications
4
46
2
Order By: Relevance
“…3 Distribution of differences between unadjusted and fair exam-level cut-scores (%) (n = 349) clinical performance (Harden et al 2015, Chapter 3;Khan et al 2013b). This finding also complements the research on the importance of examiner effects on scoring in OSCEs (McManus et al 2006;Yeates et al 2018;Yeates and Sebok-Syer 2017).…”
Section: The Impact Of Examiners On Cut-scoresmentioning
confidence: 74%
“…3 Distribution of differences between unadjusted and fair exam-level cut-scores (%) (n = 349) clinical performance (Harden et al 2015, Chapter 3;Khan et al 2013b). This finding also complements the research on the importance of examiner effects on scoring in OSCEs (McManus et al 2006;Yeates et al 2018;Yeates and Sebok-Syer 2017).…”
Section: The Impact Of Examiners On Cut-scoresmentioning
confidence: 74%
“…In one sense, having a single assessor is more likely to bring consistency to the marking of the station since all candidates will be observed by the same set of assessors across the exam. On the other hand, in small cohorts single assessors are confounded with stations and there is no easy way to directly compare assessor stringency at the station level , Yeates et al 2018. The presence of a single assessor per station (rather than multiple across circuits) may also contribute to a lack of calibration compared to a group of peers all examining the same station.…”
Section: Assessor Stringency and Assessment Designmentioning
confidence: 99%
“…Researchers filmed the simulated OSCE stations using a variety of filming methods. This included fixed, wide angle ceiling cameras (identical to filming in Yeates et al (2019); tripod based camcorders, positioned in various places within the room, and using varied degrees of zoom; head cameras worn by the examiner; and wall mounted pan/tilt/ zoom CCTV cameras positioned in various places within the room (see Figure 1). Sound was collected variously using ceiling hanging microphones; focused microphones placed on the camcorders; and table-top condenser microphones.…”
Section: Filming Approachesmentioning
confidence: 99%
“…Common to all of these approaches is the assumption that assessors' video-based judgements are equivalent to their judgements of live performances. Several studies have shown equivalent scores between live and video-based modalities (Ryan et al 1995;Vivekananda-Schmidt et al 2007;Chen et al 2019;Yeates et al 2019). This observation is not, however, universal.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation